Preparation method and application of oil-based drilling fluid wall fixing agent
A thermosensitive oil-based drilling fluid solidifier with a core-shell structure addresses the instability of oil-based drilling fluids by forming a durable gel barrier in high-temperature environments, enhancing wellbore stability and reducing drilling risks.
Patent Information
- Application Number
- CN202510476513.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-16
- Publication Date
- 2025-07-15
AI Technical Summary
Existing oil-based drilling fluids face challenges in maintaining wellbore stability due to their propensity to penetrate deep formations through microfractures and pore channels, leading to well collapse and other drilling hazards, and current sealants like asphalt and lignite have limited effectiveness at high temperatures and pressures.
A thermosensitive oil-based drilling fluid solidifier with a core-shell structure is developed, where the shell material is flexible and dispersible in the drilling fluid, forming a robust gel barrier upon temperature and pressure activation, encapsulating a core material that enhances wellbore stability by sealing micro and nano-scale fractures.
The core-shell structure effectively seals micro and nano-scale fractures, forming a durable gel layer that enhances wellbore stability, reducing the risk of well collapse and improving drilling safety and efficiency.
Smart Images

Figure BDA0005361489850000151 
Figure BDA0005361489850000161 
Figure BDA0005361489850000171
Abstract
Description
Technical Field
[0001] The present patent invention relates to the field of oilfield chemistry, and particularly to a preparation method and application of an oil-based drilling fluid wall stabilizer. Background Art
[0002] During the oil drilling process, the stability of the wellbore is crucial for the smooth progress of drilling operations. However, since the development of oil and gas resources, wellbore instability has always been one of the major technical problems in drilling engineering. Globally, billions of dollars are invested annually to address wellbore instability issues, which not only significantly increases the drilling cost but also may lead to serious economic losses and safety risks.
[0003] Although oil-based drilling fluids have been widely used in drilling operations due to their good lubricity, inhibition, and thermal stability, the problem of wellbore stability remains prominent. Microfractures, natural fractures, and pore channels in the formation provide permeation paths for oil-based drilling fluids, making it easy for them to enter deep formations, thereby triggering complex downhole accidents such as wellbore collapse and stuck pipe, and even causing wellbore abandonment, seriously threatening the safety and economic benefits of drilling operations. Research shows that the permeation behavior of oil-based drilling fluids and their physicochemical interactions with wellbore rocks are one of the main factors leading to wellbore instability. After the oil phase enters the formation microfractures and pores, the capillary tip-splitting effect will occur, resulting in the expansion and even penetration of fractures, causing the wellbore rock to exfoliate and fragment. In addition, the permeation of the oil phase may also cause the pore pressure near the wellbore to increase, weakening the supporting ability of the drilling fluid for the wellbore, thus increasing the risk of wellbore collapse. At the same time, the swelling or dissolution of the oil phase may cause deformation or dissociation of humus and clay minerals in the formation, thereby changing the stress distribution near the wellbore, significantly increasing the risk of shear slip along bedding planes or fractures, and further exacerbating wellbore instability.
[0004] Currently, asphalt and lignite are mainly used as oil-based drilling fluid plugging agents to reduce the intrusion of the oil phase into the wellbore and enhance wellbore stability. However, the plugging effects of these traditional plugging agents still have significant limitations. When the formation temperature is lower than its softening point, asphalt can effectively fill fractures and prevent the permeation of the oil phase. However, when the formation temperature exceeds its softening point, the plugging ability of asphalt will significantly decrease, and it may even be carried away by the flow of the drilling fluid, resulting in plugging failure. Although lignite has strong high-temperature resistance, its plugging ability is greatly affected by the geometric shape of fractures and stress changes, and it is difficult to form a long-term stable shielding layer, thereby reducing the inhibitory effect on the permeation of the oil phase. In addition, traditional wall stabilizers have poor stability under high temperature and high pressure conditions, and the plugging duration is limited, making it difficult to meet the requirements of wellbore stability in deep and ultra-deep oil and gas wells. Therefore, there is an urgent need to develop high-performance oil-based drilling fluid wall stabilizers to improve wellbore stability, reduce the probability of downhole complications, and provide reliable technical support for safe drilling in deep and ultra-deep shale formations. Summary of the invention
[0005] In view of the problems that existing plugging agents have a narrow temperature range and incomplete plugging effect, this study proposes a temperature-sensitive oil-based drilling fluid wall solidifier. The wall solidifier has a core-shell structure, the shell material has good flexibility, and has excellent dispersibility in oil-based drilling fluid. In the process of plugging cracks, the wall solidifier material forms an effective barrier by accumulation to prevent liquid phase invasion. At the same time, the core material is converted into a high-strength oil-based gel under the combined effect of formation temperature and pressure. The oil-based gel has a wide gelling range and good temperature resistance after gelling, thereby forming a stable shielding layer on the well wall and improving the stability of the well wall. The wall solidifier not only has no adverse effects on the operation of drilling equipment, but also provides reliable technical support for well wall stabilization, thereby promoting the efficient exploitation of oil and gas resources.
[0006] The core of the present invention is a method for preparing a core-shell structured oil-based drilling fluid wall solidifier. An oil-based drilling fluid wall solidifier is successfully prepared. The wall solidifier has a certain plugging ability and good well wall stabilization ability. It can effectively plug micro-nanoscale cracks and pores in the high temperature and high pressure environment in the shale formation, and can effectively enhance the stability of the well wall, prevent the oil phase from penetrating into the formation and causing the well wall instability problem. At the same time, the formation of gel can enhance the strength of the well wall itself.
[0007] To achieve the above-mentioned object, the present invention provides a method for preparing an oil-based drilling fluid wall solidifying agent, the method comprising: (1) preparing a prepolymer from urea, formaldehyde, nanocellulose and a curing agent to obtain a wall material mixed liquid; (2) mixing an emulsifier, a cross-linking agent, diesel, an initiator, a fiber material and an unsaturated polyester monomer to prepare a core material; reacting the wall material mixed liquid with the core material compound liquid under certain conditions, and allowing the product to stand, filter and dry to obtain an oil-based drilling fluid wall solidifying agent.
[0008] The second aspect of the present invention provides an oil-based drilling fluid wall solidifier prepared by the method described in the first aspect of the present invention, wherein the wall solidifier is a solid powder with a light color and dark gray, an average particle size of 15-55μm, a shell material temperature resistance greater than 140°C, and a temperature resistance greater than 24h.
[0009] The third aspect of the present invention provides an application of the oil-based drilling fluid wall-fixing agent described in the second aspect of the present invention under formation environmental conditions.
[0010] The fourth aspect of the present invention provides a drilling fluid, comprising the oil-based drilling fluid wall-solidifying agent of the present invention.
[0011] Beneficial effects:
[0012] Compared with the prior art, the present invention has the following beneficial effects:
[0013] (1) The present invention encapsulates the oil-based gel synthetic prepolymer within the microcapsule shell material. By utilizing the special structure of the microcapsule, the core material is released only after entering the formation, ultimately forming an oil-based gel shielding layer. This wall-building agent can be used while drilling. During the process of the drilling fluid infiltrating into the formation, due to the encapsulation effect of the shell material, the core material stays in the microfractures of the formation. As the temperature resistance time of the shell material extends, it gradually decomposes in the formation, while the core material gradually forms a high-strength gel under the formation temperature and pressure conditions.
[0014] (2) The present invention introduces nanocellulose into the microcapsule shell to improve the toughness and shear resistance of the shell material and enhance its stability in the complex wellbore environment. Formaldehyde and urea form a modified urea-formaldehyde resin under the action of a curing agent and are compounded with nanocellulose to form the shell material. During the circulation process of the drilling fluid from the drill pipe through the drill bit to the wellbore, the shear force is the strongest at the drill bit, and the contact between the drill pipe and the wellbore is also likely to cause damage to the microcapsules. Nanocellulose enhances the toughness of the shell material, keeping the microcapsules stable before entering the formation, while not affecting the release of the core material, ensuring that the gel forms a continuous body in the formation.
[0015] (3) The present invention introduces fiber materials into the core material of the wall-building agent to improve the strength and compressive resistance and high-temperature resistance of the oil-based gel. Specifically, a cross-linking agent, diesel, an initiator, and an unsaturated polyester monomer react to synthesize the oil-based gel. The strength of the oil-based gel decreases due to volume expansion, while the fiber materials can enhance the gel strength and improve the connection strength between different wall-building agents, enabling the gel in the formation to form a whole and enhancing the overall positive and reverse compressive capacities.
[0016] (4) The present invention infiltrates the oil-based drilling fluid wall-building agent into the formation in the form of microcapsules, enabling it to stay and rapidly accumulate in the microfractures of the formation to block the formation, and to a certain extent, preventing further invasion of fluids. At the same time, the microcapsule structure gives the drilling operation continuity and reduces the time cost.
[0017] (5) The present invention reduces the usage amount of the oil-based drilling fluid gel, changes the traditional slug-type application, improves its actual utilization rate, reduces the consumption of the oil-based gel, and lowers the usage cost. Description of the Drawings
[0018] Figure 1 Particle Size Distribution
[0019] Figure 2 Microscopic Observation of the Wall-Building Agent
[0020] Figure 3 Evaluation Diagram of the Plugging Effect Detailed Embodiments
[0021] The endpoints and any values in the ranges disclosed herein are not limited to the exact ranges or values. These ranges or values should be understood to include values close to these ranges or values. For numerical ranges, between the endpoint values of each range, between the endpoint values of each range and individual point values, and between individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed herein.
[0022] The following is a detailed description of the specific embodiments of the present patent invention. It should be understood that the specific embodiments described herein are only for the purpose of illustrating and explaining the present patent invention, and are not used to limit the present patent invention.
[0023] The technical solution provided by the present invention is as follows:
[0024] In the first aspect of the present invention, a preparation method of an oil-based drilling fluid wall stabilizer is provided, and the method includes:
[0025] (1) Add urea, formaldehyde, nano-cellulose, and a curing agent to water, and under room temperature conditions, mix and stir evenly to form a shell material mixed phase and form a prepolymer;
[0026] (2) Mix an emulsifier, a cross-linking agent, diesel, an initiator, a fiber material, and an unsaturated polyester monomer to form a core material mixed phase;
[0027] (3) Prepare a part of the shell material mixed phase and the core material mixed phase into an oil-in-water emulsion, and then transfer it to a three-necked flask, and heat it to the reaction temperature under the condition of uniform stirring.
[0028] (4) Then add the remaining shell material mixed phase dropwise into the three-necked flask in the form of a burette, add it dropwise to the three-necked flask, and after the dropping is completed, react for a reasonable time until the reaction ends.
[0029] (5) Dry the synthesized material at 80 °C for 24 h to form an oil-based drilling fluid wall stabilizer.
[0030] According to the present patent invention, in step (1), all stirring is carried out under ultrasonic conditions.
[0031] According to the present patent invention, in step (1), the room temperature is 15-25 °C.
[0032] According to the present patent invention, in step (1), the wall stabilizer is one or more of ammonium chloride, hydroquinone, and ammonium bicarbonate, and further preferably ammonium bicarbonate.
[0033] According to the present patent invention, in step (1), the preferred mass percentage content of formaldehyde is 10%-20% of the mass of the shell material mixed phase.
[0034] According to the present invention, in step (1), the preferred mass percentage of urea is 20%-30% of the mass of the shell material mixture phase.
[0035] According to the present invention, in step (1), the preferred mass percentage of nanocellulose is 2%-6% of the mass of the shell material mixture phase.
[0036] According to the present invention, in step (1), the preferred mass percentage of ammonium bicarbonate is 3%-7% of the mass of the shell material mixture phase.
[0037] According to the present invention, in step (1), the preferred stirring speed is 300-350 rpm / min.
[0038] According to the present invention, in step (2), the emulsifier is one or more of Tween-20, Tween-80, sodium stearate, sodium dodecylsulfonate, and sodium dodecylbenzenesulfonate. Further preferably, sodium dodecylsulfonate and Tween-20 are used in combination, and the compounding ratio is 1:1.
[0039] According to the present invention, in step (2), the preferred mass percentage of the emulsifier is 2%-3% of the mass of the core material mixture phase. Further preferably, the addition amount of the emulsifier is 2.5%.
[0040] According to the present invention, in step (2), the crosslinking agent is one or more of divinylbenzene, dibutylamine oleate, hexamethylenediamine, and 1,6-heptadiene. Further preferably, 1,6-heptadiene is used.
[0041] According to the present invention, in step (2), the preferred mass percentage of 1,6-heptadiene is 4%-6% of the mass of the core material mixture phase.
[0042] According to the present invention, in step (2), the initiator is one or more of benzoyl peroxide, lauroyl peroxide, 2,2'-azobisisobutyronitrile, and bis(2-ethylhexyl)peroxydicarbonate. Further preferably, 2,2'-azobisisobutyronitrile is used.
[0043] According to the present invention, in step (2), the preferred mass percentage of 2,2'-azobisisobutyronitrile is 0.04%-0.06% of the mass of the core material mixture phase. Further preferably, it is 0.05%.
[0044] According to the present invention, in step (2), the unsaturated polyester monomers are one or more of cinnamyl formate, tetradecyl acrylate, 4-tert-butylcyclohexyl acrylate, butyl methacrylate, butyl acrylate, n-undecyl methacrylate, and octadecyl methacrylate. Further preferably, tetradecyl acrylate and butyl methacrylate are used.
[0045] According to the present invention, in step (2), the mass percentage of preferably tetradecyl acrylate is 15%-20% of the mass of the core material mixture phase.
[0046] According to the present invention, in step (2), the mass percentage of preferably butyl methacrylate is 10%-15% of the mass of the core material mixture phase.
[0047] According to the present invention, in step (2), the fiber material is one or more of carbon fiber, silicon oxide fiber, polytetrafluoroethylene fiber, and polyimide fiber, and further preferably carbon fiber.
[0048] According to the present invention, in step (2), the mass percentage of preferably carbon fiber is 3%-5% of the mass of the core material mixture phase.
[0049] According to the present invention, in step (3), preferably a part of the shell material mixture phase is 20%-30% of the total shell material mixture phase.
[0050] According to the present invention, in step (3), when preparing the water-in-oil mixture, under the action of a homogenizer, the stirring speed is 6000 rpm / min, and homogenization and dispersion are carried out for 20 min.
[0051] According to the present invention, in step (3), the preferred reaction temperature is 60-75 °C.
[0052] According to the present invention, in step (3), the preferred stirring rate is 300-350 rpm / min.
[0053] (4) Then, the remaining shell material mixture phase is added dropwise into the three-necked flask in the form of a burette, and the dropping speed is controlled at 60 drops / min. After the dropping is completed, the reaction is carried out for 2-3 h.
[0054] According to the present invention, in step (4), preferably the remaining shell material mixture phase is 70%-80% of the total shell material mixture phase.
[0055] According to the present invention, in step (4), the preferred dropping speed is controlled at 60 drops / min.
[0056] According to the present invention, in step (4), the preferred reaction time is 1.5-2.5 h.
[0057] The second aspect of the present invention provides an oil-based drilling fluid wall stabilizer prepared by the method described in the first aspect. Among them, the wall stabilizer is a dark gray solid powder, and the average particle size is 15-55 μm, which can meet the plugging effect on microfractures in the formation.
[0058] According to the present invention, the temperature resistance of the shell material of the oil-based drilling fluid wall stabilizer is greater than 140 °C, so that the shell material can have a breakage rate of less than 80% within 16 h at 140 °C during the drilling fluid circulation process.
[0059] According to the present invention, the oil-based drilling fluid wall stabilizer can be well dispersed in the oil-based drilling fluid, is not easy to agglomerate, has a good dispersion effect, and can first block the formation microfractures under low-concentration conditions.
[0060] According to the present invention, the internal phase of the oil-based drilling fluid wall stabilizer can form an oil-based gel within 12 - 16 h. The oil-based gel molecules interact with each other to form a continuous gel body, which can delay the pore pressure transmission in the formation, improve the formation pressure-bearing capacity, and improve its forward and reverse pressure-bearing capacities.
[0061] According to the present invention, the oil-based drilling fluid wall stabilizer has little influence on the viscosity and shear force of the oil-based drilling fluid, has good compatibility, and strong adaptability.
[0062] The third aspect of the present invention provides the application of the oil-based drilling fluid wall stabilizer described in the second aspect as a wall stabilizer in the oil-based drilling fluid.
[0063] The fourth aspect of the present patent is to provide an oil-based drilling fluid, which contains the oil-based drilling fluid wall stabilizer described in the second aspect.
[0064] Examples
[0065] Example 1
[0066] (1) Add 16 g of formaldehyde, 24 g of urea, 4 g of nanocellulose, and 5 g of ammonium bicarbonate to 51 g of water. Under the condition of 25 °C and ultrasonic condition, with a stirring speed of 300 rpm / min, stir for 10 min to form a shell material mixed phase and form a prepolymer.
[0067] (2) Add 1.25 g of sodium dodecyl sulfonate, 1.25 g of Tween-20, 5 g of 1,6-heptadiene, 18 g of tetradecyl acrylate, 12 g of butyl methacrylate, 0.05 g of 2,2'-azobisisobutyronitrile, 4 g of carbon fiber, and 56.5 g of diesel. Under the condition of 25 °C, with a stirring speed of 300 rpm / min, stir for 10 min to prepare a core material mixed phase.
[0068] (3) Weigh 25 g of the shell material mixed phase and mix it with all the prepared core material mixed phase. Use a homogenizer to homogenize and disperse it for 20 min at 6000 rpm / min. Transfer the mixed emulsion to a three-necked flask and uniformly heat it to 65 °C at 300 rpm / min.
[0069] (4) Then load the remaining 75 g of the shell material mixture into a burette and add it dropwise into the three-necked flask at a rate of 60 drops / min. After the addition is complete, continue the reaction for 2 h.
[0070] (5) Dry the synthesized material at 80 °C for 24 h to form the oil-based drilling fluid wall stabilizer.
[0071] Example 2
[0072] According to the same method as in Example 1, the difference is that in step (1), the added mass of formaldehyde is 10 g and the mass of water is 57 g;
[0073] Example 3
[0074] According to the same method as in Example 1, the difference is that in step (1), the added mass of formaldehyde is 20 g and the mass of water is 47 g;
[0075] Comparative Example 1
[0076] According to the same method as in Example 1, the difference is that in step (1), the added mass of formaldehyde is 7 g and the mass of water is 60 g;
[0077] Comparative Example 2
[0078] According to the same method as in Example 1, the difference is that in step (1), the added mass of formaldehyde is 24 g and the mass of water is 43 g;
[0079] Example 4
[0080] According to the same method as in Example 1, the difference is that in step (1), the added mass of urea is 20 g and the mass of water is 55 g;
[0081] Example 5
[0082] According to the same method as in Example 1, the difference is that in step (1), the added mass of urea is 30 g and the mass of water is 45 g;
[0083] Comparative Example 3
[0084] According to the same method as in Example 1, the difference is that in step (1), the added mass of urea is 17 g and the mass of water is 58 g;
[0085] Comparative Example 4
[0086] According to the same method as in Example 1, the difference is that in step (1), the added mass of urea is 35 g and the mass of water is 40 g;
[0087] Example 6
[0088] According to the same method as in Example 1, the difference is that in step (1), the added mass of ammonium bicarbonate is 3 g and the mass of water is 53 g;
[0089] Example 7
[0090] According to the same method as in Example 1, the difference is that in step (1), the added mass of ammonium bicarbonate is 7 g and the mass of water is 49 g;
[0091] Comparative Example 5
[0092] According to the same method as in Example 1, the difference is that in step (1), the added mass of ammonium bicarbonate is 2 g and the mass of water is 54 g;
[0093] Comparative Example 6
[0094] According to the same method as in Example 1, the difference is that in step (1), the added mass of ammonium bicarbonate is 9 g and the mass of water is 47 g;
[0095] Example 8
[0096] According to the same method as in Example 1, the difference is that in step (1), the added mass of nanocellulose is 2 g and the mass of water is 53 g;
[0097] Example 9
[0098] According to the same method as in Example 1, the difference is that in step (1), the added mass of nanocellulose is 6 g and the mass of water is 49 g;
[0099] Comparative Example 7
[0100] According to the same method as in Example 1, the difference is that in step (1), the added mass of nanocellulose is 1 g and the mass of water is 54 g;
[0101] Comparative Example 8
[0102] According to the same method as in Example 1, the difference is that in step (1), the added mass of nanocellulose is 8 g and the mass of water is 47 g;
[0103] Example 10
[0104] According to the same method as in Example 1, the difference is that in step (2), the added mass of 1,6-heptadiene is 4 g and the mass of diesel is 59.5 g;
[0105] Example 11
[0106] According to the same method as in Example 1, the difference is that in step (2), the added mass of 1,6-heptadiene is 6 g and the mass of diesel is 57.5 g;
[0107] Comparative Example 9
[0108] According to the same method as in Example 1, except that in step (2), the added mass of 1,6-heptadiene is 2 g and the mass of diesel is 61.5 g;
[0109] Comparative Example 10
[0110] According to the same method as in Example 1, except that in step (2), the added mass of 1,6-heptadiene is 8 g and the mass of diesel is 55.5 g;
[0111] Example 12
[0112] According to the same method as in Example 1, except that in step (2), the added mass of tetradecyl acrylate is 15 g and the mass of diesel is 61.5 g;
[0113] Example 13
[0114] According to the same method as in Example 1, except that in step (2), the added mass of tetradecyl acrylate is 20 g and the mass of diesel is 56.5 g;
[0115] Comparative Example 11
[0116] According to the same method as in Example 1, except that in step (2), the added mass of tetradecyl acrylate is 12 g and the mass of diesel is 64.5 g;
[0117] Comparative Example 12
[0118] According to the same method as in Example 1, except that in step (2), the added mass of tetradecyl acrylate is 22 g and the mass of diesel is 54.5 g;
[0119] Example 14
[0120] According to the same method as in Example 1, except that in step (2), the added mass of butyl methacrylate is 10 g and the mass of diesel is 60.5 g;
[0121] Example 15
[0122] According to the same method as in Example 1, except that in step (2), the added mass of butyl methacrylate is 15 g and the mass of diesel is 55.5 g;
[0123] Comparative Example 13
[0124] According to the same method as in Example 1, except that in step (2), the added mass of butyl methacrylate is 8 g and the mass of diesel is 62.5 g;
[0125] Comparative Example 14
[0126] According to the same method as in Example 1, except that in step (2), the added mass of butyl methacrylate is 19 g and the mass of diesel is 51.5 g;
[0127] Example 16
[0128] According to the same method as in Example 1, except that in step (2), the added mass of butyl methacrylate is 3 g and the mass of diesel is 59.5 g;
[0129] Example 17
[0130] According to the same method as in Example 1, except that in step (2), the added mass of butyl methacrylate is 5 g and the mass of diesel is 57.5 g;
[0131] Comparative Example 15
[0132] According to the same method as in Example 1, except that in step (2), the added mass of butyl methacrylate is 2 g and the mass of diesel is 60.5 g;
[0133] Comparative Example 16
[0134] According to the same method as in Example 1, except that in step (2), the added mass of butyl methacrylate is 6 g and the mass of diesel is 56.5 g;
[0135] Example 18
[0136] According to the same method as in Example 1, except that in step (3), the total added amount of the shell material is 20 g, and in step (4), the total added amount of the shell material is 80 g.
[0137] Example 19
[0138] According to the same method as in Example 1, except that in step (3), the total added amount of the shell material is 30 g, and in step (4), the total added amount of the shell material is 70 g.
[0139] Comparative Example 17
[0140] According to the same method as in Example 1, except that in step (3), the total added amount of the shell material is 10 g, and in step (4), the total added amount of the shell material is 90 g.
[0141] Comparative Example 18
[0142] According to the same method as in Example 1, except that in step (3), the total added amount of the shell material is 40 g, and in step (4), the total added amount of the shell material is 60 g.
[0143] Experimental Example
[0144] For Example 1, particle size testing, sand bed plugging experiment, electron microscope observation experiment and compatibility experiment were carried out to evaluate the effect of Example 1. For Examples 1-19 and Comparative Examples 1-18, seam plate pressure bearing experiment and quartz sand solidification experiment were carried out.
[0145] The white oil is 5# white oil; the organoclay, main emulsifier and auxiliary emulsifier are provided by the PetroChina Engineering Institute; the oxidized asphalt and wetting agent are provided by Hubei Hanko New Technology Co., Ltd.; the calcium oxide is provided by Sinopharm.
[0146] Experimental Example 1
[0147] The solid wall agent and the wetting agent were added to the white oil, and the particle size of the solid wall agent dispersed in the white oil was measured using a laser particle size analyzer, and its dispersion degree was observed. The results showed that the D
[50] of the solid wall agent was 24 μm, and the particle size distribution was as Figure 1 shown, indicating good dispersibility.
[0148] The morphology of the solid wall agent was observed using an electron microscope, and the results were as Figure 2 shown.
[0149] The solid wall agent and the wetting agent were added to the white oil, sealed with an aging tank, and aged at 140 °C for 16 h to test the integrity of the solid wall agent. The test results showed that the breakage rate of the solid wall agent was less than 20%.
[0150] Experimental Example 2
[0151] 320 ml of white oil, 3 g of organoclay, 4 g of main emulsifier, 8 g of auxiliary emulsifier, and 6 g of wetting agent were configured as the evaluation base fluid. The plugging effects of adding the solid wall agent and the blank sample were compared, and the visual plugging effect was evaluated using a medium-pressure sand bed. The particle size of the quartz sand was 180-200 mesh, pressurized at 100 psi, and stabilized for 30 min. The results were as Figure 3 shown, where a is the sample without adding the solid wall agent and b is the sample with the solid wall agent added. The results showed that the solid wall agent could quickly plug the sand bed. The intrusion of the base fluid sample with the solid wall agent added was 11 mm, and the intrusion of the sample without the solid wall agent added was 63 mm. The oil phase intrusion amount of the sand bed with the solid wall agent added was much lower than that of the sample without the solid wall agent added.
[0152] Experimental Example 3
[0153] Seam Plate Pressure Bearing Experiment
[0154] At room temperature, first, take 300 mL of white oil, add 1% organoclay, and age it at 140 °C for 16 h. After aging, stir it at a high speed of 10,000 r / min for 20 min to prepare the base liquid. Subsequently, add 5% of the samples of the examples and comparative examples to the base liquid, and stir it at a high speed of 5,000 r / min for 20 min to obtain the final experimental samples. Fill the obtained samples into a slit plate with a size of 40–50 μm, and let it stand and age at 140 °C for 16 h. Finally, test the pressure-bearing capacity of the slit plate.
[0155] Table 1 Results of the pressure-bearing experiment of the slit plate
[0156]
[0157] As shown in Table 1, the experimental data show that the pressure-bearing capacity of the base liquid itself is 0 MPa, indicating that it has almost no pressure-bearing capacity without adding the samples of the examples and comparative examples. After adding the wall stabilizer, the pressure-bearing capacity of the "base liquid + example" group is significantly improved, ranging from 15.1–18.1 MPa, which is better than that of the "base liquid + comparative example" group. The samples added with comparative examples 1-8 were damaged before the internal gel was formed, causing the reaction mixture phase inside the microcapsules to leak out and unable to form a gel with strong stability. The pressure-bearing range is 5.2-6.9 MPa. The pressure-bearing capacity of the samples added with comparative examples 9-18 ranges from 6.4-8.6 MPa. Although the pressure-bearing capacity is better than that of comparative examples 1-8, the pressure-bearing capacity of this part of the samples is still relatively low. This indicates that the optimization measures in the examples have more advantages in improving the pressure-bearing performance of the system. Among them, Example 1 has the highest pressure-bearing capacity (18.1 MPa), followed by Example 2 (17.6 MPa) and Example 17 (17.9 MPa), which may represent the optimal formulation. In contrast, the pressure-bearing capacity of the "base liquid + comparative example" group is generally low, indicating that the modification strategies of some comparative examples failed to effectively enhance the plugging performance and may even have adverse effects. It can be seen that this drilling fluid wall stabilizer can effectively slow down the pressure transmission and play a role in stabilizing the wellbore.
[0158] Experimental Example 4
[0159] Quartz sand solidification experiment
[0160] Weigh 360 g of 80-100 mesh quartz sand, mix it with 5 g of the comparative examples and examples, place it in a cylindrical compaction container, apply a pressure of 3 MPa on it, keep the pressure stable for 2 h, and then place it in an aging furnace at 140 °C for aging for 24 h. Apply a certain pressure above the prepared sample, and record the pressure when the sample breaks. The experimental results are shown in Table 3.
[0161] Table 2 Results of the quartz sand solidification experiment
[0162]
[0163]
[0164] As shown in Table 2, the pure quartz sand mold hardly has compressive strength and fails when a pressure of 0.11 MPa is applied, indicating that its own structure is loose and it is difficult to form a stable consolidation system. After modification, the sample formed by mixing Example 1 with quartz sand exhibits the best compressive performance, with a compressive strength reaching 6.98 MPa, much higher than the samples of other examples and comparative examples, indicating that this formulation can effectively enhance the consolidation ability of quartz sand. In contrast, in Examples 2–19, due to the reduction in the dosage of some key synthetic monomers, the strength of gel formation is affected to a certain extent, resulting in a decrease in compressive strength compared to Example 1. In addition, Comparative Examples 1–8 mainly optimize the temperature resistance of the shell material and do not significantly enhance the consolidation ability of the gel. Therefore, although the compressive strength decreases, the amplitude is relatively small. In contrast, in Comparative Examples 9–18, due to the proportion of key synthetic monomers exceeding the reasonable range, the formed gel has insufficient strength, the binding ability to quartz sand particles is weakened, and the overall consolidation effect becomes poor, ultimately significantly reducing the compressive performance of the quartz sand column.
[0165] Experimental Example 5
[0166] Compatibility and wellbore stability tests of oil-based drilling fluids
[0167] (1) Compatibility test
[0168] The effects of the wall stabilizer for oil-based drilling fluids on the rheological parameters and high-temperature and high-pressure filtration loss of oil-based drilling fluids, and the compatibility test of the wall stabilizer for oil-based drilling fluids. Preparation of the base slurry: 320 ml of No. 5 white oil, 4.5 g of organoclay, 6 g of main emulsifier, 5 g of auxiliary emulsifier, 7 g of oxidized asphalt, 16 g of calcium oxide, 4 g of wetting agent, 80 ml of 35% calcium chloride aqueous solution + barite (1.80 g / cm 3 ), Drilling fluid aging treatment: Use a roller heating furnace to age the drilling fluid sample at a treatment temperature of 140 °C for 16 h. Rheological property test: After aging, stir for 20 min at 10000 r / min, and test the rheological parameters (apparent viscosity (AV), plastic viscosity (PV), and yield point (YP)) of the prepared drilling fluid according to GBT 16783.2-2014. The experimental results are shown in Table 3.
[0169] Table 3 System compatibility evaluation
[0170]
[0171] As can be seen from Table 1, adding the wall stabilizer of the present invention has little effect on the rheology of the oil-based drilling fluid, and the rheology is good, indicating that the wall stabilizer provided by the present invention has good compatibility as an additive for oil-based drilling fluids.
[0172] (2) Evaluation of gelation plugging ability
[0173] Indoor evaluation was carried out on the cementing plugging performance of "oil-based drilling fluid system + 3% of Example 1" on fractured rock samples. The experiment used artificial 3D rock samples under HTHP conditions, and dynamic shear immersion was carried out in the drilling fluid to observe the plugging situation of the rock sample fractures at different times. The experimental data are shown in Table 4:
[0174] Table 4 Experimental data of HTHP fracture
[0175]
[0176] As can be seen from Table 4, as time goes by, the fracture gradually becomes smaller. At 100 °C, it takes 15 days for the fracture to close, while at 110 °C and 120 °C, the fractures basically close in about 10 days. As the temperature increases, when it is greater than 130 °C, the fractures can basically be closed in about 7 days. That is, this system can improve the stability of the oil-based drilling fluid wellbore by effectively repairing fractures in the temperature range of 100 - 140 °C.
[0177] (3) Evaluation of the influence on rock soaking strength
[0178] Indoor, artificial simulated mudstone cores were used to carry out the change of uniaxial compressive strength of the rock under the soaking of "oil-based drilling fluid system + 3% of Example 1" at 140 °C. The experimental data are shown in Table 5.
[0179] Table 5 Influence of oil-based drilling fluid on rock soaking strength
[0180]
[0181] As can be seen from Table 5, adding a wellbore stabilizer significantly improves the soaking strength of the rock, and its strength retention rate increases from 72.95% to 92.27%. This is mainly due to the efficient plugging effect of the micro-nano material on the pores of the mudstone, which can effectively inhibit the invasion of filtrate and slow down the pressure transmission. At the same time, this material enhances the structural stability of the rock through the gelation cementing effect, thus significantly improving the stability of the wellbore.
[0182] The preferred embodiments of the present patent invention have been described in detail above. However, the present patent invention is not limited thereto. Within the scope of the technical concept of the present patent invention, various simple modifications can be made to the technical solution of the present patent invention, including any other suitable combination of each technical feature. These simple modifications and combinations should also be regarded as the content disclosed by the present patent invention and fall within the protection scope of the present patent invention.
Claims
1. A preparation method and application of an oil-based drilling fluid wall stabilizer, characterized in that, The method comprises the following steps: (1) Dissolve formaldehyde, urea, nanocellulose, and ammonium bicarbonate in water, and uniformly form a shell material mixed phase under ultrasonic conditions; (2) Dissolve sodium dodecyl sulfonate, Tween-20, 1,6-heptadiene, tetradecyl acrylate, butyl methacrylate, 2,2′-azobisisobutyronitrile, and carbon fiber in diesel oil, and mix to form a core material mixed phase; (3) Synthesize a microcapsule prepolymer from a part of the shell material mixed phase and the core material mixed phase, use a homogenizer to prepare an oil-in-water emulsion, transfer it to a three-necked flask, and heat to the reaction temperature; (4) Add the remaining shell material mixed phase to the three-necked flask dropwise. After the addition is complete, continue the reaction until the reaction ends; (5) Dry the synthesized material at 80 °C for 24 h to form an oil-based drilling fluid wall stabilizer.
2. The wall stabilizing agent for oil-based drilling fluid according to claim 1, characterized in that, The wall stabilizer has a core-shell structure. The shell material is a urea-formaldehyde modified resin, and the core material is an oil-based gel reaction monomer. The shell material and the core material form a core-shell structure material through emulsion polymerization.
3. The preparation method of the oil-based drilling fluid wall stabilizer according to claim 1, wherein The mass fraction of the shell material and the mass fraction of the core material are 1:
1.
4. The shell material part of the solid wall agent according to claim 2, wherein: The mass percentage content of formaldehyde is 10%-20% of the shell material mixed phase; the mass percentage content of urea is 20%-30% of the shell material mixed phase; the mass percentage content of nanocellulose is 2%-6% of the shell material mixed phase; the mass percentage content of ammonium bicarbonate is 3%-7% of the shell material mixed phase.
5. The core material part of the solid wall agent according to claim 2, characterized in that: The mass percentage content of 1,6-heptadiene is 4%-6% of the mass of the core material mixed phase; the mass percentage content of tetradecyl acrylate is 15%-20% of the mass of the core material mixed phase; the mass percentage content of butyl methacrylate is 10%-15% of the mass of the core material mixed phase; the mass percentage content of carbon fiber is 3%-5% of the mass of the core material mixed phase.
6. The method for preparing a wall fixing agent according to claim 1, characterized in that, In step (3), the mass percentage content of the shell material mixed phase is 20%-30% of the total mass of the shell material mixed phase, and in step (4), the mass percentage content of the shell material mixed phase is 70%-80% of the total mass of the shell material mixed phase.
7. The preparation method of the wall fixing agent according to claim 1, characterized in that, In step (4), the addition method of the shell material mixed phase is dropwise addition, and the dropping rate is 60 drops / min. After the addition is complete, the preferred reaction time is 1.5-2.5 h.
8. The oil-based drilling fluid wall stabilizer according to claim 2, wherein The oil-based drilling fluid wall stabilizer is a dark gray solid powder with an average particle size of 15-55 μm, and the temperature resistance of the shell material is greater than 140 °C.
9. The wall-building agent for oil-based drilling fluid according to claim 2, wherein, The action mode of the wall stabilizer is that first, the wall stabilizer plugs the formation. As time goes by, the internal oil-based gel mixed monomers react to form a gel, improving the integrity of the formation and enhancing the positive and reverse pressure-bearing capacities of the wellbore.
10. An oil-based drilling fluid, characterized in that, The drilling fluid contains the oil-based drilling fluid wall stabilizer described in claims 1-9.